2007
DOI: 10.1088/0741-3335/49/8/008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ion-scale dynamics on electron-temperature-gradient turbulence

Abstract: This work reports on numerical studies of small-scale electrontemperature-gradient (ETG) turbulence embedded in large-scale turbulence driven by both ion-temperature-gradient (ITG) modes and trapped-electron modes (TEM). To begin with, we find that the simplified adiabatic-ion model of ETG turbulence does not always saturate nonlinearly, suggesting that corrections to the purely adiabatic ion response are required for robust saturation. Our results also qualitatively confirm a prediction of Holland and Diamond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 16 publications
7
89
3
Order By: Relevance
“…Figure 3(a) also shows that: including electron collisions (at the experimental level) in the AI model cures the problem and considerably improves the convergence of the spectrum (the same is true for the KI model); and that with a small level of equilibrium flow shear (γ E = 0.005 v te /a) the collisionless AI simulation recovers from what appeared a catastrophically unresolved situation. The healing of the simulation, with the addition either of electron collisions or flow shear, is probably due to the stabilisation of weakly unstable trapped electron driven modes in the region k y ρ i ∼ 1, as discussed at the end of Appendix A. GYRO simulations have also found that flow shear helps in resolving ETG turbulent saturation with the AI model [32].…”
Section: Nonlinear Itg Simulations With Flow Shear For Large Aspect Rmentioning
confidence: 91%
“…Figure 3(a) also shows that: including electron collisions (at the experimental level) in the AI model cures the problem and considerably improves the convergence of the spectrum (the same is true for the KI model); and that with a small level of equilibrium flow shear (γ E = 0.005 v te /a) the collisionless AI simulation recovers from what appeared a catastrophically unresolved situation. The healing of the simulation, with the addition either of electron collisions or flow shear, is probably due to the stabilisation of weakly unstable trapped electron driven modes in the region k y ρ i ∼ 1, as discussed at the end of Appendix A. GYRO simulations have also found that flow shear helps in resolving ETG turbulent saturation with the AI model [32].…”
Section: Nonlinear Itg Simulations With Flow Shear For Large Aspect Rmentioning
confidence: 91%
“…To address this question, one would extend the validation methodology discussed so far to calculation of a local sensitivity map in which both R=L Ti and R=L Te are varied, from which a fluxmatching fractional gradient error vectorẼ z ¼ ðE LT i ; E LT e Þ could be calculated by determining the simultaneous values of R=L Ti and R=L Te which when input into the microturbulence model yield predictions of Q i and Q e that simultaneously match the power balance Q i and Q e results. While the computational resources needed to perform such an analysis using long-wavelength gyrokinetic simulations (to say, nothing of multiscale simulations which incorporate electron-scale ETG dynamics that likely contribute to Q e in many cases [65][66][67][68][140][141][142][143][144][145][146] ) over many conditions or discharges remain prohibitive for current-day computing platforms, such approaches will likely be feasible on next-generation exascale platforms. Moreover, such an approach, or even further generalizations to include matching of particle and momentum fluxes via additional variations of density and rotation gradients, is readily feasible now for most reduced turbulent transport models with fairly modest computing resources, and should be pursued further.…”
Section: E Using Flux-matching Gradients To Construct Validation Metmentioning
confidence: 99%
“…A third, even more computationally expensive avenue of approach would be to investigate the impact of multiscale simulations which self-consistently incorporate q e -scale ETG fluctuations into these q i -scale simulations. [65][66][67][68][140][141][142][143][144][145][146] Other research avenues are possible as well. However, for the goals of this paper, it should be clear how utilizing a variety of local validation metrics for multiple predicted quantities can be employed to test model fidelity and our physical understanding at a level not possible by earlier global metrics.…”
Section: Fluctuation Sensitivity Plots and Validation Metricsmentioning
confidence: 99%
“…For some C-Mod plasmas the inclusion of ETG modes can raise the electron heat transport and allow matching of both the ion and electron heat fluxes 62 . In some multi-scale simulations the presence of short wavelength modes does not qualitatively change the results for ion transport because that is dominated by strongly-driven long-wavelength ITG turbulence [74][75][76] . However, when the ion drive is sufficiently weak the inclusion of ETG modes may significantly alter the long wavelength ion heat flux 62 (and, presumably, the particle flux) so a significant role for ETG modes cannot be ruled out for the conditions examined here without further investigation.…”
Section: Turbulence Simulation Methodologymentioning
confidence: 98%